Disagreements Strategies Used In You Tube Music Commentary - Lestari, Anna Endri, Drs. Agus Wijayanto M.A., Ph.D, Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
This research aims at describing the types of disagreements strategies and the types of politeness strategies which is used in You Tube music commentary, and its intention of using disagreements. The type of this research is descriptive qualitative. The writer focuses on analyzing the types of disagreements strategies and the types of politeness strategies , that is used in You Tube music commentary. The disagreements commentary as the object of the data. The data taken are comments, sentences which contain disagreements. The source of data are taken from You Tube music commentary. The methods of collecting data are obsrevation and documentation and which the step are reading, watching, noting, and make checklist on the data. The analysis of the intentions the writer uses disagreements strategies from Anita Pomerantz (1984) and theory of politeness strategies by Brown and Levinson (1987). The result of the research show that firstly: there are 2 types of disagreements which are used You Tube music commentary, namely: Strong disagreements and Weak disagreements. The strong disagreements have 4 sub four types, namely: Strong disagreements (1) Contradiction (11,21%), (2) Challenge (10,29%), (3) Irrelevancy Claim (6,54%), (4) Counterclaim (14,02%), while Weak disagreements have 4 sub types: (5) Contradiction (3,73%), (6) Challenge (1,87%), (7) Irrelevancy claim (0,94), (8) Counterclaim (2,81). Secondly, responses to disagreements strategies used in You Tube music commentary namely: upgrade agreements and downgrade agreements. Thirdly the types of politeness strategies used in You Tube music commentary in which mostly appear is bald on record as 52%, in the second place is off record as 29%, the third place are negative politeness as 10% and the last place is positive politeness as 9%.